Efficiency and effectiveness of the COVID-19 government support: Evidence from firm-level data - Tibor Lalinsky; Rozália Pál (European Investment Bank (EIB), 2021)
We utilize several unique firm-level datasets in order to assess the efficiency and effectiveness of the government support aiming to curb the economic consequences of the coronavirus (COVID19) pandemic. The results, drawing on the experience of a small open European country (Slovakia), suggest the distributed COVID-19 subsidies save non-negligible number of jobs and sustain economic activity during the first wave of the pandemic. General distribution rules designed on the fly may bring close to optimal results, as relatively more productive, privately owned, foreign-demand oriented firms are prioritized and firms with a higher environmental footprint or zombie firms record a relatively lower chance of obtaining government funding. By assuming constant cost elasticities to sales, we show that the pandemic deteriorates strongly firm profits and increases significantly the share of illiquid and insolvent firms. Government wage subsidies somewhat mitigate firm losses and have statistically significant effect, but relatively mild compared to the size of the economic shock. Our estimates also confirm that larger firms, receiving smaller relative size of the support, have more space to cover their additional liquidity needs by increasing trade liabilities or liabilities to affiliated entities, while SMEs face higher risk of insolvencies.
Keywords: D22; H20; G32; G33; J38; 330; coronavirus; COVID-19; firm-level; policy measures; wage subsidies; profit; liquidity; solvency